Review Policy for Improving Teachers Competency: 5W+1H Analysis and Fishbone Model - Shohib, Moch (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2024)
This study provides contributions and thoughts as well as materials for evaluating curriculum implementation to be used as material for consideration in making policy directions for schools that have not implemented or have implemented Merdeka curriculum, researchers focus on the issue of implementing an Merdeka curriculum and policy directions for school principals in developing Teachers competence. This study uses a descriptive qualitative method, the research is focused on schools that have implemented the Merdeka curriculum in Lumajang, Indonesia. The data taken was taken from school principals, Teachers and educational staff at the Madrasah Tsanawiyah and Madrasah Aliyah levels using 5W + 1H which was carried out randomly. The data is then analyzed to make a fishbone diagram to find out the causes of problems in the implementation of the Merdeka curriculum. After the cause of the problem is known, the researcher formulates the principal's decision using 5W + 1H. The results of the fishbone and 5W+1H analysis show that the problem of implementing the Merdeka curriculum comes from human resources which causes the implementation of the Merdeka curriculum in schools to not be optimal. The policy direction of school principals in optimizing the implementation of the Merdeka curriculum is first by providing direct assistance, secondly by holding their own training in schools or often attending training or workshops held by the government so that the implementation of the Merdeka curriculum can run effectively and the administration of learning is fulfilled.